Co-innovation: a review and conceptual framework. (2018) - Saragih, Harriman Samuel; Tan, Jacob Donald
This paper investigates the previous theoretical and empirical studies regarding the current philosophical understandings of co-innovation and subsequently suggests a theoretical framework that exhibits the analytical pillars and the possible outputs of this notion in practice through various case studies. The analysis of this study involved examining secondary sources of scholarly literature by discussing the conceptual understandings and empirical findings on the concepts of co-innovation in several academic databases. Co-innovation is defined as a shared work of generating innovative and exceptional design conducted by various actors from firms, customers, and collaborating partners. This study proposes that there are five principal elements within the idea of co-innovation: collaboration, coordination, co-creation, convergence and complementary. The possible outputs of co-innovation can either be a new business model, new customer base, new customer value, new value chain, or new products and services. This paper attempts to evaluate the emerging concept of co-innovation and propose a conceptual framework rooted in various authentic business cases and theoretical literature.